Analysis, design and application of an appropriate teaching english methodology for pre-school children with adhd (attention deficit hyperactivity disorder) in the Bilingual Kids Centre Blue Sky - Vallejo del Castillo, Viviana Alexandra (2007)
ADHD that is characterized by hyperactivity, impulsivity and inattention is know a days investigated by many scientist that try to find the real causes of this disorder. In Ecuador the ADHD in children is not a well known theme, it is not investigated deeply, there are few teachers that discern this problem and look for a solution for applying to their daily educational job. In this investigation we can understand the possible causes of ADHD, its treatment and some methodologies that could be applied by the English teachers. With this project we can see immediately solutions so ADHD children can grow up happy and full of knowledge no matter of having this appalling disorder. This project will also make you understand the necessities of comprehending this problem; the consequences that these type of children may have if they do not care about this trouble. In the last part of the investigation you will find the developed methodology proved in a real case, with indicators and a deep analysis of the results of the methodology. One pound of learning requires ten pounds of common sense to apply it.